2012
DOI: 10.5862/mce.35.4
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the first critical load on particulate medium of sandy loam foundation

Abstract: Ключевые слова: геомеханика; механика грунтов; теория механики зернистых сред Сравнение моделей сплошной и дискретной (зернистой) сред Анализ работ различных авторов показал, что ими были рассмотрены механические явления, возникающие в грунтах при воздействии на них местной нагрузки. При этом были установлены (при давлениях на грунт, больших структурной прочности) две критические нагрузки: Р кр1 и Р кр2. Величину Р кр1 называют начальной критической нагрузкой, еще совершенно безопасной в основаниях сооружений,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Note that the behavior of the soil backfill behind the wall is more consistent discrete model (granular) environment , revealing the physical mechanism of inter granular interaction than the continuum model based on the phenomenological approach [14].…”
Section: Introductionmentioning
confidence: 87%
“…Note that the behavior of the soil backfill behind the wall is more consistent discrete model (granular) environment , revealing the physical mechanism of inter granular interaction than the continuum model based on the phenomenological approach [14].…”
Section: Introductionmentioning
confidence: 87%
“…The reduced Cosserat model can be applied for description of granular media. The theory of granular media is applicable to soil mechanics: for soils consisting of large particles and clay soils (Badanin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Practical application of these models requires an experimental determination of a large number of additional constants in the constitutive equations. There are many models for granular media (Badanin 2012, Harris 2009, Heinrich et al 1996, Kurbatskiy et al 2011). In the recent papers (Grekova et al 2004, Kulesh et al 2009) the Reduced Cosserat Continuum was suggested as a possible model to describe granular materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was proved that the loose light loams can be flowing out with the active hydraulic gradients. It was confirmed by increased opacity of the filtration water on the exit and sediment of the bearing out soils[6,7,8].…”
mentioning
confidence: 94%